PEMBIAYAAN PUSKESMAS SEBELUM DAN SESUDAH PELAKSANAAN JAMINAN KESEHATAN NASIONAL DI KABUPATEN BANYUWANGI - Perwirani; Yulita Hendrartini; Dibyo Pramono (Journal of Health Service Management, 2016)
Background: Public health center financing has increasedsince the implementation of JKN. The operational budget whichis managed by public health center is so different after theimplementation of National Health Insurance, the increasing isvery drastic. On the other hand, the local government budgetfunds is decreasing and the portion is smaller than before. Objective: To describe the financial management of publichealth center before and after the implementation of nationalhealth insurance in Banyuwangi district. Methods: The study was a descriptive case study with usequalitative data and quantitative data. Informants in this studywere 36 persons consist of 6 persons from the district healthdepartment, 3 persons from other cross sectors, and 27 personsfrom the public health centers. Those samples were taken bypurposive sampling technique. Results: There were several things that distinguish thefinancing management of public health center after theimplementation of JKN. They were the commitment from localgovernment to focus on routine operations budgeting, the morecomplicated for public health centers process of planning andbudgeting due to limited human resources and time, the lack ofinternal coordination in the public health center, the lessunderstanding from human resources on planning process, andthe lower utilization of funds from capitation due to obstruction indrug procurement process, disposable materials andregulation. Monitoring was focused on financial administration.The ANOVA test showed : 1) There was a significant differenceof realization BOK funds in public health center before and afterJKN with p = 0.0025 (p < 0.05), 2) There was a significantdifference capitation funds realization before and afterimplementation of JKN with p = 0.0016 (p < 0.05), 3) There wasno significant difference (p = 0.4257) of APBD funds realizationbefore and after the implementation of JKN. Conclusions: Implementation of JKN had impacted tofinancing management system of public health center and therewere statistically differences of realization of BOK funds andcapitation funds in public health center before and after JKN andthere was no difference of realization of APBD funds before andafter the implementation of JKN